Encouraging reflective practice through learning portfolios in an authentic online foreign language learning environment. Issue 2 (4th March 2022) - Pais Marden, M.; Herrington, Jan
ABSTRACT: This paper describes a research study that investigated foreign language student engagement in reflective practice through reflective portfolios. Over the course of one academic semester, students in an Italian as a foreign language course at an Australian university and selected target language native speaker mentors interacted and collaborated with each other in blended learning mode with the aim of completing two situated and authentic tasks designed according to an authentic learning framework. As part of the project, students wrote their observations on the progress of their collaborative work in a reflective portfolio and participated in individual and guided focus group interviews. The findings suggest that the opportunity to contribute their thoughts in writing in reflective portfolios encouraged students to reflect on their own individual learning processes and to engage in a process of collective reflection and collaborative problem solving.